DAYA DUKUNG SPASIAL KAWASAN PERTAMBAKAN MELALUI INTERPRETASI CITRA SATELIT ALOS AVNIR-2 STUDI KASUS KABUPATEN MAROS SULAWESI SELATAN - Syahrial Nur Amri; Taslim Arifin (Pusat Riset Kelautan, 2018)
Calculation of carrying capacity of aquaculture area is important to optimize the coastal area utilization. The calculations of the spatial carrying capacity require the availability of accurate spatial data, and one of the best spatial data providers today is through the use of satellite imagery. This study aims to determine the ability of the pond land in support of the coastal community activities and regional development. This research covers two stages: 1) spatially identifies the pond area through the interpretation of ALOS AVNIR-2 satellite imagery with the masking technique; 2) Calculating the value of Carrying Capacity Ratio (CCR) to know the ability of land to coastal community activities. The results show that the pond areas in Maros District identified as 9.621,60 hectares, and the CCR analysis shows a value of 2,79 or > 1. The value indicates the ability of pond land which is still relatively able to meet the needs of community activities. Bontoa sub-district is the region with the lowest CCR value (1,73), which means that the available of pond land is almost unable to fully support the community's activities. Management strategies are needed in the form of increased productivity through the intensification patterns, and / or suppressing the population growth.